Duration and decay of Arctic stratospheric vortex events in the ECMWF seasonal forecast model. (16th November 2018) - Orsolini, Yvan J.; Nishii, Kazuaki; Nakamura, Hisashi
Abstract : Previous studies have documented extreme stratospheric polar vortex events, but the factors governing their duration have received little attention. Here, we investigate weak and strong stratospheric polar vortex events simulated in ensemble reforecasts for the Northern Hemisphere winter with the seasonal forecast model (System 4) of the European Centre for Medium‐Range Weather Forecasting, in comparison with the European Reanalysis Interim dataset. The individual strong and weak vortex events are classified into short and long events. A composite analysis is conducted for each of the four categories of events with respect to their initial or end days. We examine the characteristics of each category in the forecast model and reanalyses, including anomalous zonal‐mean zonal winds, heat and wave‐activity fluxes, lower‐tropospheric temperature and surface pressure, as well as the synoptic evolution of upper‐tropospheric anomalies during the precursory and decaying stages. The main findings are: (a) the forecast System 4 is found to produce both short and long anomalous vortex events in comparable amplitude to the reanalyses, but the polar zonal wind anomalies are more persistent, for each of the four categories considered; (b) short events penetrate as deep as the long events right at their onset, but they rapidly decay under a wave forcing that is less sustained than in the long events; (c) subtle differences in the synoptic evolution of blocking Highs and Lows over both oceanic basins or over Northern Eurasia or America appear to condition the duration of the forcing; and (d) during such short events, characteristic surface or lower‐tropospheric signatures of the annular mode paradigm arising from the downward stratospheric influence are not allowed sufficient time to develop. Abstract : We examine how the seasonal forecast system from ECMWF reproduces short and long stratospheric polar vortex events, in comparison to reanalyses, and investigate factors governing their duration and decay. We show that the forecast model is over‐persistent and that short events penetrate as deep as the long events right at their onset. During such short events, characteristic signatures of the annular mode paradigm arising from the downward stratospheric influence are not allowed sufficient time to develop.